Encourage resource governance: Responding disaster threats behind environmentally friendly claims at the Tumpang Pitu gold mine - Theresia Octastefani; Bayu Mitra A. Kusuma; Niko Pahlevi Hentika (Universitas Islam Malang, 2022)
The Indonesian constitution has stated that natural resources must be utilized for the people’s benefit. But the people’s interests are often defeated by the elite. The long-term goal of this research is not to close the mining area and its activities, but to ensure that the exploration and exploitation process that has already started must prioritize ecological balance and disaster resilience. Using a qualitative method and a descriptive approach, this study analyzes the role of the government, corporation, and local communities in the framework of resources governance in order to strengthen the advocacy of civil society who are often marginalized in the existence of extractive industries. The results of the study show that the gold mining activity is contrary to the forestry law where the existing rules have been liberalized by selling state assets to private companies; the lack of added value for local communities such as limited job vacancies; the occurrence of environmental damage around the gold mining area where this area is actually a protected forest and a natural barrier from the threat of a tsunami disaster; and even though mining companies have claimed that their activities are environmentally friendly, in fact disasters are starting to appear.